PEMESANAN TIKET WISATA DI KABUPATEN KUNINGAN BERBASIS MOBILE - Ismasari Nawangsih; Elgi Ginanjar (Jurnal SIGMA, 2019)
The current development of information technology is a human need in carrying out daily activities or activities, with the development of technology and its proper use it will produce appropriate information, especially in the ease of obtaining information on booking tourist tickets in Kuningan Regency for migrants such as the community. outside Kuningan Regency. This online-based tourist ticket booking information system is a digital startup centered on the service sector, an online-based ticket booking information system using an Android mobile. With the existence of this online ticket booking service, it is hoped that it can help customers in making it easier to order tickets according to what the customer expects. The purpose of making this online-based ticket booking information system is to make tourism in Kuningan Regency easily promoted, as well as extensive network access. This system development method uses the SDLC (System life cycle) method which is a classic methodology used to develop, maintain, and use information systems, for the system testing method here uses the blackbox testing method The blackbox testing method is a program testing stage that prioritizes testing of functional requirements of a program. The result of the conclusion of this online-based ticket booking information system is to make it easier to get tourist tickets in Kuningan Regency. Keywords : Ticket ordering information system, ticket booking, SDLC (System life cycle) method.